Extraction and analysis of aerosol anomalies associated with multiple shallow earthquakes based on MODIS AOD products - Ping Lu; Xiao Gao; Zhixuan Xiong; Yu Shang (International Journal of Applied Earth Observations and Geoinformation, 2025)
Shallow earthquakes are among the most devastating natural hazards, and aerosol anomalies offer insights into crust–atmosphere interactions critical for earthquake forecasting and environmental assessment. However, standardized anomaly extraction protocols—especially whether to center analyses on epicenters or fault zones—remain undefined, and the driving mechanisms of these anomalies are insufficiently studied. This work utilizes MODIS AOD retrievals and a background field–based Robust Satellite Technique (RST) algorithm to detect AOD anomalies linked to 14 global shallow-focus earthquakes using a 2σ threshold, followed by statistical significance testing (p < 0.05). Spatiotemporal analysis of five representative events reveals that higher-magnitude earthquakes generate stronger (up to 6.28σ) and longer-lasting (≥4 days) AOD perturbations. AOD peaks follow a consistent spatial hierarchy: marine > coastal > inland. Marine anomalies cluster around fault zones; coastal anomalies appear as discrete points near faults; inland anomalies show pre-seismic, banded distributions migrating toward epicenters. By employing buffer zones of 0.5°, 1°, and 2°, we isolated pre- and post-seismic AOD anomalies across diverse tectonic settings. The results suggest that a 1° buffer is the optimal spatial window for most earthquake cases. Micro–scale diagnostics via aerosol classification maps and particle–size distribution metrics identified shifts between fine– and coarse–mode particles, while macro–scale HYSPLIT–4 backward–trajectory analyses elucidated the roles of local topography, anthropogenic emissions, and dust storm inputs on anomaly formation. These findings advance our understanding of seismic aerosol perturbations and inform the development of integrated remote–sensing frameworks for earthquake monitoring and environmental impact assessment.